The Effect of the Flipped Classroom Strategy on Learning Some Basic Football Skills for Second Grade Middle School Students - Oudah, Ammar; Atallah , Waad Mohammed (Pubmedia Jurnal Pendidikan Olahraga, 2026)
The study identifies the effect of the flipped classroom strategy and the command method in learning certain basic skills in football for second-grade students in the middle stage, and the preference of the effect between the flipped classroom strategy and the command method in learning some skills in football. The experimental method was used with the pre- and post-tests to fit the research problem as the best way to achieve its goals. The study population was (90) intermediate students of the second-grade intermediate leadership. The study sampled (60) students who were selected through the lottery system for the two divisions (A, C), and they represent 66% of the original population, and the most important results of the research were - The flipped classroom strategy is superior to the command method in the performance of rolling and handling skills of the second grade students in the middle stage.- Enhancing the positive role of the student, achieving harmony with the study material, and creating a spirit of competition and enthusiasm, which led to an increase in classroom interaction.